Resolvent for Non-Self-Adjoint Differential Operator with Block-Triangular Operator Potential - Aleksandr Mikhailovich Kholkin (Abstract and Applied Analysis)
A resolvent for a non-self-adjoint differential operator with a block-triangular operator potential, increasing at infinity, is constructed. Sufficient conditions under which the spectrum is real and discrete are obtained.